(untitled) (Sudurpaschim Spectrum, 2024)
This paper investigates the root causes of contemporary environmental crises, attributing them to an anthropocentric perspective that views nature merely as a resource for human exploitation. This mindset has led to the depletion of natural resources, loss of biodiversity, and widespread pollution, resulting in an unsustainable ecological balance. In response, the paper advocates adopting Arne Naess’s "Deep Ecology" to restore harmony between humans and nature. Deep Ecology emphasizes that all life possesses intrinsic value, and humans must coexist within the interconnected web of life. To address these crises, a non-anthropocentric approach that allows nature to thrive without undue human intervention is essential. This interconnectedness can be sustained through the environmental ethic of care and love espoused by eco-feminist perspectives. To substantiate these claims, the paper critically analyzes Rabindranath Tagore’s short story "Bolai - The Boy and the Tree" and Thomas Hardy’s poem "The Darkling Thrush" to reveal the concept of double exploitation of nature, women, and children, as well as human "spiritual autism" and the inability to communicate with nature. Additionally, it examines the award-winning documentary "Honeyland" (2019), highlighting Haditze, the female protagonist, as a "guardian angel" who fosters a symbiotic relationship with nature based on care and love. Employing a qualitative research paradigm with close reading of texts and content analysis, the study incorporates relevant insights from researchers and scholars. By advocating for these philosophies, the paper aspires to a future where humans coexist harmoniously with the natural world, safeguarding Earth’s ecosystems for future generations and emphasizing the need for further research into this vital connection.